Long-term cost-effectiveness of glass hybrid versus composite in permanent molars. (September 2021) - Schwendicke, Falk; Basso, Matteo; Markovic, Dejan; Turkun, Lezize Sebnem; Miletić, Ivana
Abstract: Objectives: We assessed the long-term cost-effectiveness of glass hybrid (GH) versus composite (CO) for restoring permanent molars using a health economic modelling approach. Methods: A multi-national (Croatia, Serbia, Italy, Turkey) split-mouth randomized trial comparing GH and CO in occlusal-proximal two-surfaced cavities in permanent molars (n=180/360 patients/molars) provided data on restoration failure and allocation probabilities (i.e. failure requiring re-restoration, repair or endodontic therapy). Using Markov modelling, we followed molars over the lifetime of an initially 12-years-old individual. Our health outcome was the time a tooth was retained. A mixed-payers' perspective within German healthcare was used to determine costs (in Euro 2018) using fee item catalogues. Monte-Carlo-microsimulations, univariate and probabilistic sensitivity analyses were conducted. Incremental cost-effectiveness ratios (ICER)s and cost-effectiveness-acceptability were quantified. Results: In the base-case scenario, CO was more effective (tooth retention for a mean (SD) 54.4 (1.7) years) but also more costly (694 (54) Euro) than GH (53.9 (1.7) years; 614 (56 Euro). The ICER was 158 Euro/year, i.e. payers needed to be willing to invest 158 Euro per additional year of tooth retention when using CO. In a sensitivity analysis, this finding was confirmed or GH found more effective and less costly. Conclusion: CO was more costly and limitedly more effective than GH, and while there is uncertainty around our findings, GH is likely a cost-effectiveness option for restoring permanent molars. Clinical significance: When considering the long-term (life-time) cost-effectiveness, GH showed cost savings but CO was limitedly more effective. Overall, cost-effectiveness differences seems limited or in favour of GH.